AWARENESS ABOUT MENSTRUAL HYGIENE AMONG ADOLESCENT GIRLS IN RURAL AREA OF KANCHEEPURAM DISTRICT –TAMIL NADU - DR.R.UMA DEVI; DR.C.SIVAGURUNATHAN; DR.P.MOHAN KUMAR (International Journal of Pharma and Bio Sciences, 2016)
Research Question: How the menstrual hygiene practices among rural adolescent girls were performed? Rural area under rural health training centre of Sree Balaji Medical College and Hospital, Padappai, Kancheepuram District,Tamilnadu. A community based cross sectional study. Participants: 180 adolescent girls Padappai comprises about 4 schools of which 3 private schools and one government school. Permission was obtained from government school and all the students from age group 11 to 16 were taken as study sample. Results: Age ranged from 11 to 16 years for attainment of menarche. Only 43.33% girls were aware regarding menstruation prior to the attainment of menarche. Mother was found to be the first source of information regarding menstruation in 57.69% of girls. 35.55% girls reported use of old cloth for protection during menstruation. 77.77% girls were restricted to attend religious occasions during menstruation.